Peranan kitab jawi tasawuf sebagai medium transmisi ilmu Islam kepada masyarakat Melayu nusantara - Faudzinaim Hj Badaruddin, (Universiti Kebangsaan Malaysia, 2012)
Kitab Jawi has been known to have played a vital role in transmitting the knowledge of Islam to the Malay people in the Malay Indonesian Archipelago since fifteenth century AD. It has been used by the Malay scholars as a medium of education in imparting the knowledge and understanding of Islam. Nonetheless, its importance has been underestimated by some scholars as irrelevant and insignificant. Thus, this article provides an overview on the important aspects of the Kitab Jawi in Sufism as a source of Islamic knowledge on sufism and as an intermediary role of this genre in transmitting the opinion of the Muslim scholars from the al-Haramayn, the centre of Islamic knowledge, and the Malay people in the Archipelago.